The Pragmatic function of the herald in Surat Al-Baqarah - said oda, Huda; صادق غالب , أ.م.د. جاسم (Basra studies journal, 2023)
The study aims to clarify the meaning of the pragmatic herald function contained in the functional grammar through an introductory study of it, its conditions and characteristics, as well as distinguishing it from the herald in the old Arabic grammar by mentioning the common points and distinguishing features between them, and knowing its parsing and its location according to the functional grammar . The application of this to Surat Al-Baqarah, in which the deliberative function of the herald is mentioned in several places; Being one of the long surahs in the Noble Qur’an, it included all the other deliberative functions mentioned in the functional grammar. The focus was on the components to which the function of the herald is assigned, fulfilled with the conditions and qualities mentioned in the functional grammar.